Innovation of Ceiling Plaster Gun - Hassan Ismail; Juliawati Jama’on; Hairy Omar; Nur Hizyan Syazira Idrus; Siti Nuraishah Yusri; Muhammad Zulhelmy bin Rosli; Nur Aqilah binti Nizam (POLITEKNIK NEGERI JAKARTA, 2023)
Finishing is the final work in the building work element. A delicate and neat finish can describe the status of the building as well as provide a liven up the space. The quality of the finish depends on the finishing method and the tools used while doing the finishing. One of the finishing works is plastering the ceiling. Plastering the ceiling is a way to cover the surface using cement plaster, lime plaster or gypsum. Plastering the ceiling aims to cover defects on the original surface of a ceiling in order to highlight the tidiness and provide protection to the ceiling. The initial surveys obtained by the Department of Public Work (PWD) and construction workers at Taman Merlimau Emas Seksyen 1 , it’s found that the problem faced by theirs non-ergonomic ceiling plastering work. This is because this work requires the process of taking mixed plaster from the mixing bucket as well as the process of levelling the plaster on the ceiling by using existing tools repeatedly which can lead to the risk of Musculoskeletal Disorders (MSDs). The objective is to innovate Ceiling Plaster Gun. Secondly, to measure the suitability of the product from the aspect of time taken during ceiling plastering, layer of plaster layer and product design. The effectiveness of this product is to ensure whether this product can be used in the long term or not. Therefore, the tests carried out to measure the effectiveness by comparing existing tools and our products are by conducting on-site tests. In addition, a questionnaire was also conducted to construction workers who use our products to test the effectiveness of the Ceiling Plaster Gun. Overall, the existing plaster tools have a lack of effectiveness compared to the Ceiling Plaster Gun which is able to reduce the risk of Musculoskeletal Disorders (MSDs).